Schrödinger’s dilemma: «What is life?» - San Miguel De Pablos, José Luis (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
For a long time the attempt to define «life» was more a philosophical than a scientific preoccupation. Yet the importance of this question has been recognized by more philosophically-minded scientists such as physicist Erwin Schrödinger, who had some brilliant insights in this regard. In his little book What is Life? (1944) he proposed that molecular biology and the elimination of entropy by human beings would be the two pillars of the biology of the future. Schrödinger juxtaposed the theories of reductionism and holism in his inspired work, although he failed to attain a satisfactory synthesis. Nevertheless his epilogue includes an unexpected twist: a third perspective focused on the existence of consciousness. In the article it is suggested that the General Theory of Systems (TGS), which is explained and justified by Far-Equilibrium Thermodynamics, could provide the means to attain a fully satisfactory conception and definition of life, on the condition that the third perspective of Schrödinger (i.e., the link between life and consciousness) is taken into account. This idea was important to Teilhard de Chardin and absolutely central to Alfred North Whitehead.